Sensory Properties of Yellow Pumpkin Dodol with the Addition of Soy Protein Isolate - Asep Dodo Murtado; Ade Vera Yani; Idealistuti Idealistuti; Putri Regina Prayoga (Universitas Muhammadiyah Palembang, 2024)
One of the traditional foods that is popular among several Indonesian communities is dodol. Processed food is made from a mixture of white glutinous rice flour, sugar, and coconut milk, which is boiled until it becomes thick and non-sticky with a dense and chewy texture.The aim of this research was to determine the best yellow pumpkin dodol based on sensory properties with the addition of soy protein isolate.The method used was a Randomized Block Design (RAK) method arranged in a non-factorial manner with five treatments, namely T0 (pumpkin dodol without the addition of soy protein isolate), T1 (addition of 2% soy protein isolate), T2 (addition of 4% soy protein isolate), T3 (addition of 6% soy protein isolate), and T4 (addition of 8% soy protein isolate). The research results showed that the addition of soy protein isolate had a significant effect on color,taste, and texturebut had no significant effect on aroma. The most preferred treatment was T0 (pumpkin dodol without the addition of soy protein isolate) with an average characteristic value of color (3.60) and aroma (3.48), the most preferred treatment was T1 (yellow pumpkin dodol with the addition of 2% soy protein isolate)with an average value of taste characteristics (4.16); and the most preferred treatment was T4 (pumpkin dodol with the addition of 8% soy protein isolate) with an average value of texture characteristics (4.24